The effect of alexithymia on self-perceived aging among community-dwelling older adults with multiple chronic conditions: the mediating role of maladaptive cognitive emotion regulation strategies - Xu, Jianou; Shang, Bin; Zhang, Jun; Luo, Caifeng; Bian, Zekun; Lv, Fei (Frontiers in Psychiatry, 2024)
ObjectivesThis study investigated the mediating role of maladaptive cognitive emotion regulation strategies in the relationship between alexithymia and self-perceived aging among older adults.MethodsWe surveyed 478 Chinese community-dwelling older adults from November 2022 to May 2023. The Toronto Alexithymia Scale (TAS-20), Cognitive Emotion Regulation Questionnaire (CERQ), and Brief Aging Perceptions Questionnaire (B-APQ) were used. Correlation analyses, multiple linear regression analysis, and structural equation modeling were performed.ResultsThe average age of participants was 71.52 ± 7.80 years, and the number of chronic diseases was distributed as follows: 270 (56.49%) had 2 disease conditions, 156 (32.64%) had 3 disease conditions, and 52 (10.88%) had 4 disease conditions or more. Scores for alexithymia 57.83 ± 10.19; maladaptive cognitive emotion regulation strategies 49.63 ± 10.65; and self-perceived aging 58.74 ± 10.23. Alexithymia and maladaptive cognitive emotion regulation strategies were positively correlated with negative self-perceived aging (r=0.665 and r=0.673, respectively), explaining 51.8% of the variance in self-perceived aging. Structural equation modeling results showed that alexithymia had a direct effect (of 0.368) on self-perceived aging, accounting for 44.1% of the total effect. Maladaptive cognitive emotion regulation strategies partially mediated the relationship, with a mediation effect of 0.386, accounting for 51.8% of the total effect.ConclusionThese findings suggest that addressing maladaptive cognitive emotion regulation strategies can help reduce negative self-perceived aging in elderly individuals with multiple chronic conditions, particularly among those with alexithymia.